2007
DOI: 10.1007/s12103-007-9014-y
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Job Satisfaction: A Survey of Alabama Policing

Abstract: This study examines police job satisfaction and its association with general occupational attraction. Police officers from sixteen municipal departments (n=1,114) across one southern state (Alabama) were found to possess moderate-high overall job satisfaction, with regression analysis supporting the conclusions of prior studies that demographics are of little value to understanding job satisfaction. The findings convey that 25% of job satisfaction variance can be explained from six variables (in order of impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 28 publications
4
63
1
Order By: Relevance
“…(Spector 2008). e other researcher in their study found that work environment is also a superior predictor of employee job satisfaction in the organization setting (Reiner and Zhao, 1999;Carlan, 2007;Ellickson and Logsdon, 2001;Forsyth and Copes, 1994). Moreover variation exists in terms of pay packages, working conditions, incentives, recognition and fringe bene ts for the employees (Lavy, 2007).…”
Section: Impact Of Promotion On Job Satisfaction and Employee Turnovermentioning
confidence: 94%
“…(Spector 2008). e other researcher in their study found that work environment is also a superior predictor of employee job satisfaction in the organization setting (Reiner and Zhao, 1999;Carlan, 2007;Ellickson and Logsdon, 2001;Forsyth and Copes, 1994). Moreover variation exists in terms of pay packages, working conditions, incentives, recognition and fringe bene ts for the employees (Lavy, 2007).…”
Section: Impact Of Promotion On Job Satisfaction and Employee Turnovermentioning
confidence: 94%
“…Notwithstanding the impact that environmental factors related to the work itself exert on employees' job satisfaction (Ellickson and Logsdon 2001;Carlan 2007;Abdulla et al 2011;Tlaiss 2013), the current study is aimed at investigating the relationship between personal demographic variables and job satisfaction in Lebanon. Exploring this relationship is important, given the scarcity of similar studies in Lebanon and the conflicting and inconclusive results that have been reported to that end in studies conducted in the Middle East.…”
Section: Major Studies On Job Satisfaction In the Arab Middle Eastmentioning
confidence: 99%
“…public image, frustration with the judicial system) on employee satisfaction (Abdulla et al, 2011;Boke and Nalla, 2009;Carlan, 2007;Chiva and Alegre, 2008;Coman and Evans, 1988;Davey et al, 2001;Dick, 2011;Griffin and McMahan, 1994;Hwang, 2008;Johnson, 2012;MacKain, Myers, Ostapiej and Newman, 2010;Allen, 1991, Meyer andHerscovitch, 2001;Miller, Mire and Kim, 2009;Morris, Shinn and Dumont, 1999;Nalla, Rydberg and Meško, 2011). Abdulla et al (2011) andCarlan (2007) found that environmental factors (in our study they are listed among the organizational factors; "salary and incentive" was the most powerful determinant of employee satisfaction) are the key determinants of employee satisfaction compared to demographic ones and that both intrinsic and extrinsic factors can be a source of employee satisfaction. MacKain et al (2010) established that salary, perceived organizational support and relationships emerged as being important to overall satisfaction and that the (general) facet "management" (i.e.…”
Section: Antecedents Of Employee Satisfaction: Empirical Studies Condmentioning
confidence: 99%